IMPACT OF AN EDUCATIONAL INTERVENTION ON KNOWLEDGE OF HEALTH CARE PROFESSIONALS REGARDING HIV-AIDS IN LAHORE, PAKISTAN - Manzoor, Iram; Khan, Fawadia; Navied, Umbreen; Abbas, Syed Muslim (Journal of Ayub Medical College Abbottabad, 2019)
Background: The Acquired Immunodeficiency Syndrome (AIDS) is a disease associated with stigmatization and discrimination worldwide. Even the health care professionals show negative attitude towards these patients. Worldwide need of health education is felt to address the gap in knowledge and attitude of health care professionals while dealing with patients suffering from this disease. Methods: It was an educational interventional study, conducted in Fatima Memorial College of Medicine and Dentistry in 2015. The sample was collected through Non-Probability purposive technique, targeting both male and female health care professionals interested in attending health education sessions on HIV-AIDS. A self-administered questionnaire was used to assess the knowledge of thirty participants for pre- and post- intervention. Results: The study participants included public health professionals (50%), dentists (16.7%) and clinical professionals (33.3%). A significant difference was observed in knowledge of health care professionals after intervention considering the important reasons as deteriorating moral value (p=0.045) for HIV epidemic in Pakistan, prevalence status of HIV/AIDS (p=0.046), awareness about the free voluntary counselling and testing (VCT) centres /services (p=0.019), interaction with an HIV positive person (p=0.01), discriminatory attitudes due to family member (p=0.032) and availability of services for people living with HIV in Pakistan (p=0.02). Conclusion: Health educational intervention is a powerful tool for increasing awareness of health care professionals. Keywords: Healthcare professionals, Education intervention, HIV/AIDS